Complicated urinary tract infection caused by Corynebacterium urealyticum – a pathogen that should not be forgotten - Omar, Mohd Khairul Izzati; Che Hussin, Nurzam Suhaila; Awang Hamat, Rukman (Malaysian Medical Association, 2022)
Although Corynebacterium urealyticum has rarely been isolated in diagnostic laboratories, this bacterium can be a significant uropathogen causing significant complications. It causes cystitis and alkaline encrusted cystitis, commonly involved in patients who need prolonged hospitalization and bladder catheterisation. We report here a case of a 19-year-old young man who was diagnosed with N-Methyl D-aspartate receptor (NMDAR) encephalitis that requires hospitalization for optimization of rehabilitation treatment in Hospital Kuala Lumpur, Malaysia. His urine culture isolated slow growing gram-positive pleomorphic rods subsequently identified as C. urealyticum. Based on the risk factors, the isolation of C. urealyticum could not be simply dismissed as contaminants. The patient was treated successfully with vancomycin for two weeks.